The significance of innovation networks in the formalisation of urban agriculture as an urban land use: the case of Johannesburg - Zivhave, Morgen (My University, 2019)
Mainstream debates show the continued marginalisation of traditional urban agriculture (UA) by conventional land use planning despite its food security, nutrition, environmental and social benefits globally. Instigated by observed tensions (and resultant vicious cycle) between UA and land use planning in Johannesburg, this study poses innovation as a means for UA to navigate the city’s neoliberal market-driven logic and land use planning. The study argues for the need for innovation by both sectors but takes a step further by drawing on the innovation networks theory to argue the case for a collaborative ecosystem of actors. Literature shows that improving products, services and organisational practices by UA is not sufficient to secure land access in cities. The study uses the market logic within the neoliberal environment, juxtaposing international case studies to explore UA’s place in contemporary Johannesburg. The study used the extended case study approach to gather experiences from UA entities, City of Johannesburg and collaborating partners. The method regards participants as shaping and simultaneously being shaped by the external forces; and thus innovation networks between UA and land use planning practices are mirrored within the broader national neoliberal planning policy. Similar to Almere, Berlin, Detroit, Havana and Portland, the key study findings are that applying the principles of innovating networks to Johannesburg creates a collaborations ecosystem between UA and land use planning actors that attract investment and enhances value addition which in turn leads to formalisation of the sector (thus translating to a virtuous cycle). However, despite these collaboration platforms, neoliberal planning pressures have reversed UA formalisation in the cities of Berlin and Portland as urban farms are converted to real estate. With the exception of Almere, experiences in Havana and Detroit shows the success of innovation networks in permanently zoning UA outside the neoliberal planning pressures. Regrettably, the neoliberal planning paradigm focuses on the economic viability of UA and discounts its social, health, environmental and food security benefits to the local economy.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy in Town and Regional Planning, University of the Witwatersrand, October 2019
Keywords: Technological innovations--Economic aspects; Information networks; Economic development